Characterising socially accountable research: a scoping review protocol paper - David Marsh; Erin Cameron; Maxwell Kennel; Kerri Z Delaney; Jennifer Dumond; Jessica Jurgutis; Alex Georges Anawati; Joseph Leblanc (BMJ Open)
Introduction Social accountability is a key value and aspirational goal of many medical institutions. While much has been studied on social accountability in the context of medical education and institutions, less research has examined how social accountability influences research. In light of this absence, the objective of our scoping review is to research the following questions: (1) What characterises socially accountable research (SAR), and how is it expressed and experienced? (2) How do language, positionality, and worldview influence SAR?, and (3) What structures and considerations are necessary to support successful SAR in local and global contexts?Methods and analysis To answer the above research questions, the Arksey and O’Malley, Levac et al, Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews and Joanna Briggs Institute (JBI) guidelines will be followed. The search strategy was adapted and applied to MEDLINE, Embase, ERIC, and CINAHL databases. A total of n=5289 eligible articles were identified. Articles were excluded if they were published before 1995, were in a language other than English, or were duplicates, leaving n=2840 articles for title/abstract screening.Ethics and dissemination Ethical approval is not required to complete this study. We will take an integrated knowledge translation approach. Throughout the project, results will be disseminated to knowledge users (ie, consultations, following Arksey and O’Malley). Our findings will be presented to the larger academic community, policymakers, and healthcare practitioners through presentations, reports, newsletters, and an online repository.Trial registration number Open Science Framework 16 July 2024. osf.io/mvhnu.